The combination of daptomycin with β-lactam antibiotics is more effective than daptomycin alone for vancomycin-resistant Enterococcus faecium bloodstream infection - Yu-Chung Chuang; Jann-Tay Wang; Jia-Ling Yang; Chi-Ying Lin; Sung-Hsi Huang; Yee-Chun Chen; Shan-Chwen Chang (Elsevier, 2022)
Background: The treatment options for vancomycin-resistant Enterococcus (VRE) are limited. A combination of daptomycin (DAP) and β-lactam (BL) has been suggested; however clinical studies supporting this are lacking. Methods: Patients with VR E. faecium bacteremia who received ≥ 8 mg/kg daptomycin for ≥ 72 h and initiated ≤ 5 days of culture collection between 2010 and 2021 were included. DAP+BL was defined as receiving BL for ≥ 24 h and within 24 h of DAP initiation. The primary endpoint was a composite clinical success (neither 14-day mortality, microbiological failure, nor change in the anti-VRE regimen). Outcomes were analyzed using multivariable logistic regression and augmented inverse probability weighting (AIPW). Results: A total of 430 patients were enrolled (DAP, n = 45; DAP+BL, n = 385). Clinical success was achieved in 19 (42.2%) patients in the DAP group and 244 (63.4%) in the DAP+BL group [adjusted odds ratio, 3.19; 95% confidence interval (CI) 1.61-6.33; P = 0.001]. Marginal analysis showed that the efficacy of DAP+BL was particularly significant with DAP dose ≥ 9 mg/kg and DAP minimum inhibitory concentration (MIC) ≥ 2 mg/L. With the balance of AIPW, standardized mean clinical success rates for DAP and DAP+BL 37.3% and 63.5%, respectively. The difference between DAP+BL and DAP was of 26.2% in favor of DAP+BL (95% CI, 10.0-42.3%; P = 0.001). Conclusions: DAP+BL was associated with a significantly higher rate of compositive clinical success than DAP for treatment of VR E. faecium bacteremia. The study suggested BL in combination with high-dose DAP for VR E. faecium bacteremia treatment, especially when VRE showed a high DAP MIC.